A study on outcome of various K-wire fixations in paediatric supracondylar humerus fractures - Shah, Shalin Bharat; Parikh, Kushal Nikhil; Paraliya, Pradipkumar Ishvarbhai (International Journal of Research in Orthopaedics, 2020)
Background: The ideal pin geometry for treatment of paediatric supracondylar humerus fracture is still debated. Various studies have been carried out comparing medial-lateral pinning (MLP) and lateral only pinning (LOP), but none have compared all three individually i.e. MLP, lateral divergent pinning and Lateral Trans olecranon fossa four cortex purchase pinning (TOF-FCP). This study aims to compare the cosmetic and functional outcome of these three pinning methods. Methods: 54 children with supracondylar humerus (Gartland type 2 or 3) meeting inclusion criteria were treated operatively and followed up till 6 months postoperatively. At 6 months the cosmetic and functional outcomes were assessed using the modified Flynn criteria. Results: All fractures united within 3 to 6 weeks duration. The mean duration of fracture union was 4.05 weeks. Functional outcome was satisfactory (i.e. excellent or good) at 6 months according to Flynn criteria in 95% of cases in cross pinning, 100% cases in TOF-FCP construct and 89% cases in lateral entry divergent pinning. cosmetic outcome was satisfactory (i.e. excellent or good) at 6 months according to Flynn criteria in 95% of cases in cross pinning, 100% cases in TOF-FCP construct and 89% cases in lateral entry divergent. Conclusions: Functional and cosmetic outcome of all three pinning geometries after operative intervention of paediatric supracondylar humerus fracture is similar in expert hands. The incidence of complications with TOF-FCP construct is less amongst the lateral only pinning.